Photoprotection and Photostability of a New Lignin-Gelatin-Baccharis antioquensis-Based Hybrid Biomaterial (2021)
ABSTRACT: The aim of this study was to develop a new hybrid biomaterial that could photo-stabilize and improve the photoprotective capacity of a Baccharis antioquensis extract. Different combinations of lignin/gelatin/natural extract were applied to prepare hybrid biomaterial nanoparticles (NPs), which were then incorporated into an emulsion. The in vitro photoprotection and photostability were evaluated. The methanolic extract showed high phenolic content (646.4 9.5 mg GAE/g dry extract) and a DPPH radical assay revealed that the antiradical capacity of the extract (0.13 to 0.05 g extract/mmol DPPH) was even better than that of BHT. The particle size of the hybrid biomaterial ranged from 100 to 255 nm; a polydispersity index (PdI) between 0.416 and 0.788 is suitable for topical use in dermocosmetic products. The loading capacity of the extract ranged from 27.0 to 44.5%, and the nanoparticles (NPs) showed electrostatic stability in accordance with the zeta potential value. We found that the formulation based on lignin: extract (1:1 ratio) and gelatin: lignin: extract (0.5:0.5:1 ratio) demonstrated photoprotection qualities with a sun protection factor (SPF) ranging from 9.4 to 22.6. In addition, all the hybrid NP-formulations were time-stable with %SPFeff and %UVAPFeff greater than 80% after exposure to 2 h of radiation. These results suggest that the hybrid biopolymer-natural extract improved the photoprotection and photostability properties, as well as the antiradical capacity, of the B. antioquensis extract, and may be useful for trapping high polyphenol content from natural extracts, with potential application in cosmeceutical formulations.